(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Sonneratia spp. was genetically unique genera. They had some members in Java, especially Sonneratia alba and S. caseolaris. This species have ability to cross reproduction, and produce fertile hybrid, although the fertility is lower than the parent, so they hard to differÂ morphologically. This research had been done in 6 sites (populations) of the southern and northern coast of Java, i.e. Bogowonto estuary, Kulonprogo (1 pop.), Segara Anakan, Cilacap (2 pops), coast of Pasar Bangi, Rembang (1pop), Juwana estuary, Pati (1 pop), and Canal Wulan estuary, Demak (1 pop). The research indicated that S. alba was more dominant, but there were some confused in morphological character, that may be caused by hybridization. Isozymic analyses on peroxidase and esterase marker to 60 individuals (10 per population) had been no differing in isozymic band significantly. They have similarity index value more than 60%. It indicated, that they tend to same species than separate it. Keywords: isozyme, diversity, Sonneratia, northern and southern coast of Java.